Acceptance Factors and Psychological Investigation of Clinical Trials in Cancer Patients - Jiangjie Sun; Jingyi Fang; Chenchen Zhang; Nannan Jia; Weiming Zhao; Jinjian Gao; Yingying Huang; Jiqing Hao; Liping Zhang (Behavioural Neurology)
Aim. To understand the degree of oncology patients’ awareness of drug clinical trials and oncology patients’ willingness to participate in drug clinical trials and the factors influencing them. Methods. The differences in the relevant variables of patients’ willingness to accept clinical trials were analyzed, and a descriptive analysis was done for the measurement data (mean and standard deviation). Pearson’s correlation coefficient analysis was used to examine the correlation between willingness and the demographic variables. Stepwise regression analysis was used to explore the influencing factors of patients’ willingness to accept clinical trials. Results. There were no statistical differences in age, gender, education level, marital status, place of residence, monthly income, medical payment method, and treatment time (P>0.05). Patients’ willingness to accept drug clinical trials differed in their cognitive degree of clinical drug trials (P=0.002). Patients’ willingness to accept drug clinical trials differed in their experience in clinical trials (P<0.001). The correlation difference was statistically significant. The willingness to accept drug clinical trials was negatively correlated with treatment time (R=−0.16, P<0.05) and positively correlated with awareness of clinical trials and whether they had been subjects (R=0.16 and 0.43, P<0.05). Multiple regression analysis showed that patients’ willingness was directly influenced by age, treatment time, and whether they had been subjects (F=21.315, P<0.001). Conclusion. Age, treatment time, and whether they had been subjects were the direct influencing factors of patients’ willingness. This study pointed out that hospitals should do a good job in the publicity of clinical trials of new drugs, expand publicity channels, increase publicity efforts, improve the awareness of clinical trials of the masses, and promote the enthusiasm of the masses to participate in clinical trials of drugs.